The first one-pot ambient-temperature synthesis of 1, 2, 4-oxadiazoles from amidoximes and carboxylic acid esters. Issue 7 (16th February 2017) - Baykov, Sergey; Sharonova, Tatyana; Shetnev, Anton; Rozhkov, Sergey; Kalinin, Stanislav; Smirnov, Alexey V.
Abstract: The first one-pot room-temperature protocol for the synthesis of 3, 5-disubstituted-1, 2, 4-oxadiazoles via the condensation between amidoximes and carboxylic acid esters in superbase medium MOH/DMSO is reported. A broad spectrum of alkyl, aryl and hetaryl amidoximes and esters was examined. This reaction route provides convenient access to 1, 2, 4-oxadiazoles, which is highly desirable because in the light of this privileged scaffold is recognized as an important core in the design of novel therapeutic agents and high-tech materials. Graphical abstract: Highlight: The advantages of novel protocol for 1, 2, 4-oxadiazole synthesis: high yields, mild conditions & simple work-up procedure.